Immune Monitoring of Patients Treated With a Whole-Cell Melanoma Vaccine Engineered to Express 4-1BBL. Issue 8 (October 2016) - Engelstein, Roni; Merims, Sharon; Eisenberg, Galit; Cohen, Jonathan; Frank, Stephen; Hamburger, Tamar; Frankenburg, Shoshana; Ron, Ilan; Isacson, Ruth; Grenader, Tal; Steinberg, Hanna; Cohen, Cyrille J.; et al.
Abstract : CD8 lymphocytes are mandatory mediators of tumor regression. To enhance their specific antitumor activity, we aimed to improve a melanoma cell-based vaccine by transfecting it with 4-1BB ligand, a costimulatory and immune modulatory molecule. Thirty-four American Joint Committee on Cancer (AJCC) stage IIB–IV patients were vaccinated with a melanoma antigen-rich cell line engineered to express HLA-A2 and 4-1BBL (M20/A2/BBL). Twelve serially recruited patients were monitored for interferon γ expression and CD107a mobilization before and after vaccination. Thirty-three patients remained alive, with an estimated mean overall survival of 26.2 months. No grade 3–4 adverse events were encountered. Immune monitoring detected an increase in circulating antimelanoma CD8 T cells in 9 of 12 patients, which were significantly stimulated by the parental melanoma, reflecting a relevant antitumor response. The results from this study show that the costimulatory 4-1BB ligand fortifies an antigen-rich melanoma cell line with enhanced antigen-specific stimulation of CD8 T cells. The use of a costimulatory molecule as part of a vaccine confers a selective increase of T-cell subsets with antimelanoma reactivity, which in some cases were characterized for their epitope specificity. Abstract : Supplemental Digital Content is available in the text.